Vulcanized polymeric cathode material featuring a polyaniline skeleton for high-rate rechargeability and long-cycle stability lithium-sulfur batteries. (20th June 2018) - Tsao, Chih-Hao; Hsu, Chun-Han; Zhou, Jing-De; Chin, Chia-Wei; Kuo, Ping-Lin; Chang, Chien-Hsiang
Abstract: A novel vulcanized polymeric cathode (S@h-P) is prepared by an inexpensive, simple heat treatment of polyaniline with sulfur particles for lithium–sulfur batteries. Conventional lithium–sulfur batteries easily dissolve free polysulfides, which causes a long-term stability issue; therefore, modified separators and polysulfide absorbents are necessary. In this work, sulfur atoms form covalent bonds with aromatic rings of the polyaniline backbone, and so no free polysulfides from the novel cathode exist, as confirmed by XRD and DSC. From CV analysis, the S@h-P only exhibits lower-order polysulfide on the polymer backbone, which affects the charge-discharge profile during the cell test. S@h-P exhibits a satisfactory cyclic stability of 88% capacity retention after 200 cycles, and it offers the excellent rate performance of 55% capacity preservation at the current density of 10 A g −1 compared to 0.1 A g −1 . Most interestingly, this polymeric cathode can function in a carbonated system, whereas conventional lithium–sulfur batteries can not. Accordingly, the novel S@h-P cathode can be employed to fabricate ultra-stable and high-performance lithium–sulfur batteries for practical application.